Verdi's La Traviata - Piave, Francesco Maria, 1810-1876 (Opera classics library., 2005)
A comprehensive guide to Verdi's LA TRAVIATA, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 30 music highlight examples.